2015
DOI: 10.1007/s12035-015-9122-5
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insights into NeuN: from Neuronal Marker to Splicing Regulator

Abstract: Neuronal nuclei (NeuN) is a well-recognized "marker" that is detected exclusively in post-mitotic neurons and was initially identified through an immunological screen to produce neuron-specific antibodies. Immunostaining evidence indicates that NeuN is distributed in the nuclei of mature neurons in nearly all parts of the vertebrate nervous system. NeuN is highly conserved among species and is stably expressed during specific stages of development. Therefore, NeuN has been considered to be a reliable marker of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
134
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(153 citation statements)
references
References 100 publications
11
134
0
1
Order By: Relevance
“…3a,b). NEUN is a marker of mature neurons2021; however, consistent with previous observations222324, distribution of NEUN immunofluorescence was heterogeneous in the SCN, with stronger expression in a central region and minimal expression in dorsal and medial regions (Fig. 3a,b).…”
Section: Resultssupporting
confidence: 90%
“…3a,b). NEUN is a marker of mature neurons2021; however, consistent with previous observations222324, distribution of NEUN immunofluorescence was heterogeneous in the SCN, with stronger expression in a central region and minimal expression in dorsal and medial regions (Fig. 3a,b).…”
Section: Resultssupporting
confidence: 90%
“…Positive staining for NeuN suggests the neuronal nature of neoplasms and is considered to be a reliable marker for clear cell neoplasms of the central nervous system, which include CN, oligodendroglioma, and clear cell ependymoma [48889]. It has also been reported that positive staining for NeuN correlates with a lower proliferation index [490].…”
Section: Histopathological Analysis and Molecular Pathogenesismentioning
confidence: 99%
“…In human, RBFOX3 is a protein-coding gene located on chromosome 17 and comprised of 15 exons [14]. As the third member of the RNA-binding fox family of proteins, RBFOX3 plays a role in alternative pre-mRNA splicing via binding to the conserved UGCAUG element in the upstream intron [15].…”
Section: Introductionmentioning
confidence: 99%